Difficulties experienced by the informal caregiver and their coping skills in the daily care of the elderly with Alzheimer's disease (Research, Society and Development, 2022)
Objective: to know the difficulties experienced by the caregiver in the daily care of the elderly with Alzheimer's disease. Methodology: a study with exploratory characteristic performed through an integrative literature review, we used the descriptors Alzheimer's disease, elderly health and combined caregivers. Results: it was initially verified in the PUBMED, LILACS, SCIELO and MEDLINE 1,565 publications database and 111 studies were evidenced by the years of publication. From the articles found, after eligibility analysis, 11 articles were selected for the preparation of this review. Conclusion: the difficulties are related to maintaining communication, memory changes, aggressiveness and activities of daily living. It is necessary that caregivers know the disease to understand the patient and, consequently, the possibilities of action (safe and effective) to this patient. This is possible through continuing education and implementation of psychoeducational programs capable of providing information and practical guidance to improve the care offered by caregivers to patients with Alzheimer's disease.